The Origins of the Shi‘a: Identity, Ritual, and Sacred Space in Eighth-Century Kufa By Najam Haider (New York: Cambridge University Press, 2011. 278 pages.) (American Journal of Islam and Society, 2013)
This book will be of interest to scholars in a variety of fields and disciplines:Islamic studies (history, thought, institutions, and modern developments), history,religion, anthropology, and sociology, to name a few that immediatelycome to mind. The book’s great virtue lies in its bringing together two heretoforesomewhat antagonistic or apparently mutually exclusive scholarly temperamentsto focus on a problem (or rather a cluster of problems) of the very first importance, articulated as the title of a seminal article by one of the greatminds of the last century engaged in the academic pursuit of Islamic history:How did the early Shi‘a become sectarian?Marshal Hodgson’s interest and task in that complex and erudite study(published in 1955) has been admirably continued and, in a real sense, consummatedin this excellent book. One of the many reasons the question aswell as the answers it may generate are so important (even urgent, one mightadd) is because to ask how the early Shi‘a became sectarian is also to askhow Sunni Islam eventually came to be configured in its classical and enduringform, how Sufism arose, and how Islam acquired its singular cosmopolitanprofile frequently characterized by the perhaps spurious prophetichadith: ikhtilOEf ummati raúmah (Disagreement in my community is a divinemercy) ...